Kebijakan Pemerintah Dalam Penentuan Kontrak Gross Split Sektor Minyak Dan Gas Di Indonesia - Edy Soesanto; Abdullah Rizky Agusman; M. Mahlil Nasution; Siti Fadhillah (Jurnal Bhara Petro Energi, 2023)
As a solution to the problem of the Cost Recovery production sharing contract system, the Government of Indonesia through the Ministry of Energy and Mineral Resources issued Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 08 of 2017 concerning Gross Split Production Sharing Contracts. This new regulation is motivated by the low number and length of time it took for oil and gas reserves to be discovered, accompanied by Non-Tax State Revenue (PNBP) for the upstream oil and gas sector which continues to decline. The Gross Split production sharing contract scheme also offers a reduction in bureaucracy in investing which is expected to attract investors to carry out exploration and exploitation in Indonesia. This study aims to analyze the legal principles related to Gross Split regulations in the aspect of improving the investment climate for upstream oil and gas and analyze the new role of the Oil and Gas Special Task Force as an institution appointed by the state to exercise control and supervision of the activities of Cooperation Contract Contractors in Sharing Contracts.